Effectiveness of stiffness on vortex induced vibration for energy harvesting - Fong, Jonathan Weixiang. (2013)
Due to the recent trend of energy conservation and harvesting, there is an increased in the recent development of the area in energy conversion devices by the means of water vortex induced vibration. There are a few methods of energy conversion, it can be from a water turbine, a water wheel or a cleaner greener and simpler way is by Vortex Induced Vibration (VIV). Vortex Induced Vibration is a new method of energy harvesting, higher VIV would resulting in a higher energy harvesting. Thus further in depth study is required to understand the basic mechanisms and fundamental methods to optimally harvest the energy with the best possible configuration.